2018
DOI: 10.3390/nu10111584
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Malaysian Adults’ Energy and Macronutrient Intakes to National Recommendations: A Review and Meta-Analysis

Abstract: The present study examined the best available evidence regarding energy and macronutrient intake during adulthood (age 19 to 59 years) in Malaysia and assessed whether intakes adhere to national recommendations, in order to develop recommendations for dietary improvement based on population consumption patterns. A literature review and meta-analysis evaluated intake based on the following characteristics, using information from food balance sheets, national surveys, and individual studies: (1) levels of intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Based on the analyses of HEI components, women in the present study had low HEI component score for legumes and milk and milk products, with the average score ranging from 1.04 to 3.83. This is consistent with the findings of a review and meta-analysis on energy and macronutrient intakes of Malaysian adults which showed that most Malaysians did not meet the recommended servings for other protein sources specifically legumes, nuts, milk and milk products [46].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the analyses of HEI components, women in the present study had low HEI component score for legumes and milk and milk products, with the average score ranging from 1.04 to 3.83. This is consistent with the findings of a review and meta-analysis on energy and macronutrient intakes of Malaysian adults which showed that most Malaysians did not meet the recommended servings for other protein sources specifically legumes, nuts, milk and milk products [46].…”
Section: Discussionsupporting
confidence: 90%
“…Asian countries, such as China [55], Singapore [13], and Indonesia [15] have adapted the HEI and AHEI-P to the local dietary guidelines. These measures of HEI were also associated with sociodemographic characteristics [53,54,56], pre-pregnancy weight status [12,16], and birth outcomes [46,57,58]. The HEI for Malaysians used in this study showed an association with GWG, thus, giving support to HEI as a good indicator of diet quality in this study population.…”
Section: Discussionsupporting
confidence: 56%
“…A higher level of 4HPLA in the males of this study may imply an increased consumption of protein-rich foods. The claim is corroborated by a meta-analysis that found higher protein intake in Malaysian males than females [ 31 ]. However, the inference remains to be verified as dietary patterns were not examined in the current study.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, a high protein intake in pregnant and lactating women in Malaysia followed the same intake pattern of Malaysian adults. A recent review by Shahar et al ( 77 ) indicated that the total protein intake among Malaysian adults remained higher than the national recommendation. The consumption of excessive-high protein food source might develop the risk of diet-related diseases and impact fetal development.…”
Section: Discussionmentioning
confidence: 97%
“…The risk of bias assessment was modified from Shahar et al ( 77 ) that was specifically developed for nutrition science (i.e dietary assessment). The following information was rated: selection bias (sampling method used and representative of pregnant and lactating women); performance bias (dietary assessment method and measurement of usual intake); and reporting bias (excluded or included over/under-reporters and paid database/primary data collection).…”
Section: Methodsmentioning
confidence: 99%